Yesterday's News: A Temporal Discontinuity in the Sting of Inferiority. (May 2019) - Kristal, Alexander C.; O'Brien, Ed; Caruso, Eugene M.
Reactions to other people who get desirable outcomes should be a simple function of how much one desires those outcomes. Four studies ( N = 4, 978) suggest that one's reactions depend on the temporal location of outcome acquisition: Observers care more (e.g., feel more envy) right before, versus right after, other people have identical experiences (Studies 1, 2a, and 2b). For example, participants' envy in February rose as Valentine's Day approached (as a peer's enviable date loomed in the future) but abruptly plateaued come February 15 onward (after the date occurred). Further, the passing of time specifically assuaged the pain of comparison (whereas positive reactions, such as feeling inspired, remained high; Studies 3a, 3b, and 3c); therefore, taking a past perspective can be used to regulate negative emotions in the present (Study 4). Time asymmetrically shapes the experience of upward comparison, despite other people's desirable outcomes indeed being achieved. Other people's good lives sting less if they have already lived them.